Strategi Pengembangan Ekowisata Kawasan Taman Wisata Alam Pulau Pombo - Meity Pattipawaej; Henderina Lelloltery; Jusmy D Putuhena (Jurnal Hutan Tropis, 2026)
This research was conducted at the Pombo Island Nature Tourism Park in Central Maluku Regency. The method used to determine the ecotourism development strategy is SWOT analysis. The Pombo Island Nature Tourism Park (TWA) area serves a dual function for environmental conservation as well as education, research, and sustainable tourism activities. Strategies that can be developed as alternatives for ecotourism development in the Pombo Island Nature Tourism Park include: setting affordable ticket prices as a primary attraction for online promotion; developing conservation-based tour packages; optimizing the potential of natural beauty through digital promotion; and strengthening digital branding through collaborations with transportation operators to improve tourist accessibility.